How Can Smoking Cessation Be Induced Before Surgery? A Systematic Review and Meta-Analysis of Behavior Change Techniques and Other Intervention Characteristics - Prestwich, Andrew; Moore, Sally; Kotze, Alwyn; Budworth, Luke; Lawton, Rebecca; Kellar, Ian (Frontiers in Psychology, 2017)
Background Smokers who continue to smoke up to the point of surgery are at increased risk of a range of complications during and following surgery. Objective To identify whether behavioural and/or pharmacological interventions increase the likelihood that smokers quit prior to elective surgery and which intervention components are associated with larger effects. Design Systematic review with meta-analysis. Data Sources MEDLINE, Embase and Embase Classic, CINAHL, CENTRAL. Study Selection Studies testing the effect of smoking reduction interventions delivered at least 24 hours before elective surgery were included. Study appraisal and synthesis Potential studies were independently screened by two people. Data relating to study characteristics and risk of bias were extracted. The effects of the interventions on pre-operative smoking abstinence were estimated using random effects meta-analyses. The association between specific intervention components (behaviour change techniques; mode; duration; number of sessions; interventionist) and smoking cessation effect sizes were estimated using meta-regressions. Results Twenty-two studies comprising 2992 smokers were included and 19 studies were meta-analysed. Interventions increased the proportion of smokers who were abstinent or reduced smoking by surgery relative to control: g = 0.56, 95% CI 0.32 - 0.80, with rates nearly double in the intervention (46.2%) relative to the control (24.5%). Interventions that comprised more sessions, delivered face-to-face and by nurses, as well as specific behaviour change techniques (providing information on consequence of smoking/cessation; providing information on withdrawal symptoms; goal setting; review of goals; regular monitoring by others; and giving options for additional or later support) were associated with larger effects. Conclusion Rates of smoking can be halved prior to surgery and a number of intervention characteristics can increase these effects. There was, however, some indication of publication bias meaning the benefits of such interventions may be smaller than estimated. Registration Prospero 2015: CRD42015024733